Development Strategy Of Peh Pulo Beach As A Sustainable Tourism Destination In Sumbersih Village, Panggungrejo Subdistrict, Blitar Regency - Syahrani, Tirana Devi; Dienaputra, Reiza D.; Hermanto, Bambang (Graduate School, Universitas Brawijaya, 2026)
Coastal tourism has significant potential to stimulate economic growth and improve community welfare in Indonesia’s coastal areas. Sumbersih Village in Panggungrejo Subdistrict, Blitar Regency, is home to Peh Pulo Beach, a coastal attraction characterized by white sandy beaches and a pristine natural environment. Despite its high tourism potential, the development of Peh Pulo Beach remains suboptimal due to inadequate road accessibility, limited supporting facilities, weak digital promotion, and constrained human resource capacity in tourism management. This study aims to formulate development strategies for Peh Pulo Beach as a sustainable tourism destination based on local social, economic, and environmental conditions. A qualitative research approach was employed through in-depth interviews with two key informants, the Head of Peh Pulo Hamlet and a local resident who serves as the village office caretaker, supported by field observations and documentation. Data were analyzed using the Miles and Huberman interactive model, consisting of data condensation, data display, and conclusion drawing. The findings indicate that poor accessibility, insufficient tourism facilities, and the absence of structured digital promotion are the main barriers to tourism development, while strong community support constitutes a critical enabling factor. Therefore, strategic priorities include improving access infrastructure, enhancing tourism facilities, empowering local communities, strengthening digital promotion, and addressing regulatory barriers to support sustainable tourism development.